Characterisations of force and pressure fluctuations of real vehicles. (2016) - Cadot, O.; Courbois, A.; Ricot, D.; Ruiz, T.; Harambat, F.; Herbert, V.; Vigneron, R.; Délery, J.
Both the unsteady aerodynamics force and base pressure distributions are investigated for four model cars in real flow conditions. The low pass cut-off frequency of the measurements is about 5 Hz which is sufficient to consider the global fluctuations of drag, lift and side forces. The drag fluctuations are very low, they never exceed 1% of the mean drag. A clear correlation is found with the base pressure distribution fluctuations. It is found that the regions of smallest pressure fluctuations on the vehicle base are the most correlated to the drag fluctuations or in other words, the regions of largest pressure fluctuations on the base are not associated with the drag fluctuations. Sideslip effect is studied, and one of the models presented a clear bistable behaviour on the lift creating huge fluctuations as investigated in the academic experiment of Grandemange et al. (2013b).